2014
DOI: 10.1111/pcmr.12236
|View full text |Cite
|
Sign up to set email alerts
|

Notch signaling in the pigmented epithelium of the anterior eye segment promotes ciliary body development at the expense of iris formation

Abstract: The ciliary body and iris are pigmented epithelial structures in the anterior eye segment that function to maintain correct intra-ocular pressure and regulate exposure of the internal eye structures to light, respectively. The cellular and molecular factors that mediate the development of the ciliary body and iris from the ocular pigmented epithelium remain to be fully elucidated. Here, we have investigated the role of Notch signaling during the development of the anterior pigmented epithelium by using genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…We have recently shown that JAG1 and NOTCH2 regulate CB fold formation by maintaining cell proliferation and BMP signaling in the OCE (Zhou et al, 2013). Inactivating the NOTCH downstream transcriptional factor RBPJ in the CB also consistently leads to the complete CB loss and eye degeneration, whereas constitutive Notch signaling increases IOP due to CB hyperplasia (Sarode et al, 2014). However, it remains unclear why the Rbpj mutant CB causes more severe eye phenotypes than the Notch2 mutant CB.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently shown that JAG1 and NOTCH2 regulate CB fold formation by maintaining cell proliferation and BMP signaling in the OCE (Zhou et al, 2013). Inactivating the NOTCH downstream transcriptional factor RBPJ in the CB also consistently leads to the complete CB loss and eye degeneration, whereas constitutive Notch signaling increases IOP due to CB hyperplasia (Sarode et al, 2014). However, it remains unclear why the Rbpj mutant CB causes more severe eye phenotypes than the Notch2 mutant CB.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the genes listed in the etiology section, a putative causal gene that can be added to this list is Notch1 [79]. This gene encodes the Notch1 receptor as part of the Notch pathway, and in humans resides on chromosome 9q34.3.…”
Section: Futurementioning
confidence: 99%
“…A recent report investigating the development of the anterior pigmented epithelium of the ciliary body indicated that the Notch pathway could play a role in iris development [79]. The notable findings were that loss of canonical Notch signaling, through Notch 2 or RBJ absence, results in normal iris development and absence of the ciliary body, while Notch1 gain-of-function result in aniridia with ciliary body hyperplasia, the latter causing glaucoma-like disease.…”
Section: Futurementioning
confidence: 99%
“…Cloning of ASD mutations in mice has led to identifying ASD genes in humans (Kuo et al, 2012; McKeone et al, 2011). Additionally, many phenotypes characteristic of ASD—ciliary body and trabecular meshwork hypoplasia, peripheral iridocorneal adhesion, buphthalmos, and elevated IOP—have been found in both spontaneous and genetically modified mouse mutants (Chang et al, 2001; Gould et al, 2007; Kroeber et al, 2010; Libby et al, 2003; Mao et al, 2011; Sarode et al, 2014; Smith et al, 2000; Sowden, 2007; Weng et al, 2008; Zhou et al, 2013). Mutations in transcription factors ( PITX2 , FOXC1 , FOXF2 , LMX1B , PAX6 ) are responsible for numerous cases of ASD and PCG (Gould et al, 2004b) and mouse mutants have been used to study the cell biology of these genes in the eye.…”
Section: Glaucoma-relevant Anterior Segment Diseasementioning
confidence: 99%